MITICIDAL ACTIVITY OF METHANOLIC EXTRACT OF VITEX NEGUNDO-LAM AGAINST SARCOPTES SCABIEI IN ANIMALS AND MAN - M. A. Khan; A. H. Shah; A. Maqbol; N. Khan; Z. U. Rahman (Journal of Animal and Plant Sciences, 2012)
The present study was designed to determine the miticidal effect of methanolic extract from Vitex negundo Lam. at the rate of 10 and 20% concentrations through topical application on scabies affected skin of camel, buffalo, goat, dog and man. The ivermectin was used as reference compound and100% methyl alcohol as control group. The topical application of the treatment groups on scabies affected buffalos gave 43, 73 ,81 and 0%, on camels 46, 75, 84 and 0% on dogs 42, 77, 83 and 0%, on goats 42, 69, 81 and 0% and on man 61, 78, 84 and 0% protection, respectively, after 5th weeks of application. In addition, the effect of Vitex negundo methanolic extract with three different concentrations (10, 20, and 30%) was studied in vitro to determine the potential to kill Sarcoptes scabiei. The results revealed that 10, 20 and 30% concentrations of Vitex negundo methanolic extract caused 70, 80, and 90% mortality of the Sarcoptes scabiei mites, respectively in comparison to ivermectin and methyl alcohol that gave 85 and 5% mortality, respectively. It is concluded that methanolic extract of Vitex negundo Lam was found good as ivermectin a proven miticide both in vitro and in vivo
Keywords: Vitex negundo; methanolic extract; mite; ivermectin; Sarcoptes scabiei